Gestão da saúde no trabalho: uma experiência institucional - Schmidt, Maria Luiza Gava [UNESP]; Barbosa, Walnei Fernandes; Biazotti, Kátia Aparecida; Toledo, Maria Luisa M. B.; Pinceli, Silva Cristina (My University, 2012)
This article aims to disseminate the results of a university action which occurred through the Extension Course entitled Management and Health at Work, conducted from March to September 2011 and offered by “Coordenadoria de Saúde e Segurança do Trabalhador e Sustentabilidade Ambiental” (a kind of Workers' health and safety and environmental sustainability agency) - an agency managed by “Pró-Reitoria de Administração - PRAd/Unesp”. This action had the audience of the technical and administrative staff of the several Institutes (Units) of UNESP in positions of Leadership and Supervision. The course was proposed to equip managers to deal with issues related to health and safety at work in daily labor. Six hundred managers of all UNESP Institutes participated in the course. The meetings were logistically designed respecting the proximity of the participants’ Institutes. The methodology adopted was based on qualitative techniques such as group discussion, role-plays, analysis of film, reading and discussing texts, together with the preparation of a proposal for health promotion by the participants. As a result it was considered that the course offered a convenient and timely opportunity to reflect on and discuss the theme of health and safety at UNESP, as well as to make leaders and managers effective agents to implement programs of disease prevention and health promotion at work.

Este artigo tem como objetivo difundir os resultados de uma ação universitária que ocorreu por meio do Curso de Extensão intitulado Gestão e Saúde no Trabalho, oferecido pela Coordenadoria de Saúde e Segurança do Trabalhador e Sustentabilidade Ambiental, órgão da Pró-Reitoria de Administração - PRAd/Unesp, realizado no período de março a setembro de 2011. Esta ação teve como público-alvo os servidores técnicoadministrativos das Unidades da Unesp que ocupam cargos de Chefia e Supervisão. A proposta do curso foi instrumentalizar gestores para lidar com questões relacionadas à saúde e segurança no trabalho no cotidiano laboral. Participaram do curso seiscentos gestores de todos os câmpus. Para atender os participantes, os encontros foram logisticamente delineados respeitando a proximidade das Unidades. A metodologia adotada foi embasada em técnicas de natureza qualitativa como discussão em grupo, sociodrama, análise de filme, leitura e discussão de textos, somadas à elaboração de uma proposta de promoção da saúde pelos participantes. Como resultado considerou-se que o momento do curso foi oportuno para refletir e discutir sobre a temática da saúde e segurança no trabalho, no âmbito da Unesp, transformando o gestor num agente multiplicador para implementação de programas de prevenção de doença e promoção da saúde no contexto laboral.
Keywords: Health at Work; Management; Prevention; Health Promotion; Acidentes do trabalho; Capacitação; Condições e organização do trabalho; Gestão em saúde